2006
DOI: 10.1007/s00426-006-0081-3
|View full text |Cite
|
Sign up to set email alerts
|

Using geometry to specify location: implications for spatial coding in children and nonhuman animals

Abstract: The study of spatial cognition has benefited greatly from a technique known as the disorientation procedure. This procedure was originally used with rats to show that they relied on the geometry of an enclosed space to locate a target hidden in that space. Disorientation has since been used with a variety of mobile animals, including human children, to examine the coding of geometric information. Here, we focus mostly on our recent work with young children. We examine a set of issues concerning reorientation--… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 65 publications
(73 reference statements)
1
13
0
Order By: Relevance
“…During recent years, however, there have been numerous demonstrations of even toddlers relying on geometric information about the shape of an enclosed space to locate a target object hidden at one of the corners of the space (e.g., Hermer & Spelke, 1994, 1996; for reviews, see Cheng & Newcombe, 2005;Lourenco & Huttenlocher, 2007). Despite the growing literature, questions concerned with how toddlers process location information such as geometry have been difficult to answer.…”
Section: Introductionmentioning
confidence: 97%
“…During recent years, however, there have been numerous demonstrations of even toddlers relying on geometric information about the shape of an enclosed space to locate a target object hidden at one of the corners of the space (e.g., Hermer & Spelke, 1994, 1996; for reviews, see Cheng & Newcombe, 2005;Lourenco & Huttenlocher, 2007). Despite the growing literature, questions concerned with how toddlers process location information such as geometry have been difficult to answer.…”
Section: Introductionmentioning
confidence: 97%
“…Research has shown that although human children and nonhuman primates are robust navigators, they do not use maps or precise distances to navigate to a location [3,5]. It is suggested that they instead use mental transformations to overcome changes in perspective and to make general assessments about the direction in which they must move to reach a certain location.…”
Section: Related Workmentioning
confidence: 99%
“…The Bonobo being observed had to travel from a start location to a designated goal; it did not take a rigid trajectory but varied its path [4]. Starting position did not affect its ability to successfully navigate, implying it possesses the ability to mentally encode the "entire spatial layout" of the area, and can mentally manipulate this encoding to localize itself and travel appropriately [5].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Their Wndings support the helpfulness of using a landmarkbased strategy, which has the advantage of being computationally simpler than using path integration-based survey knowledge. Lourenco and Huttenlocher (2006) contrast the use of landmarks and of the geometric properties of an environment within which people are moving, as cues on which they rely in spatial learning. By using a variety of disorientation procedures, they challenge the view that young children rely primarily on geometrical information to reorient themselves in enclosed spaces and suggest that they actually code information about their own positions relative to the spatial environment.…”
mentioning
confidence: 97%